SISTEM PENUNJANG KEPUTUSAN SELEKSI JABATAN PIMPINAN TINGGI PRATAMA DI KABUPATEN KATINGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Oktaviyani, Enny Dwi; Sahay, Abertun Sagit; Pradana, Arie (Universitas Palangka Raya, 2017)
Selection system positions of High Leadership Of Pratama in Katingan Regency whoseimplementation stage is still using manual or traditional way. A High Leadership Of PratamaCandidate must go down directly to obtain information on the selection process and stages. At thecompletion stage of the file administrative requirements are also still done manually is submitted tothe selection committee in the form of printed documents and in the process of calculating the valueand ranking done, the selection committee is still using the manual way. This certainly makes itdifficult for the selection committee to verify the administrative requirements file and perform theprocessing of data value because the number of candidates of High Leadership Of Pratama whoregister relatively much so it will take time, energy is not small and prone to errors. Therefore it isnecessary media that can facilitate all the stages and can help decision making.Decision Support System Selection Position of High Leadership Of Pratama In KatinganRegency With Simple Additive Weighting Method built using waterfall methodology. The stages in thewaterfall methodology to build a software are needs analysis, system design, program code writing,program testing and maintenance. And in the process of making the system using the programminglanguage Adobe Dreamweaver CC 2017 as a PHP editor and website page editor and for data storageusing MySQL. With Xampp as a localhost server application. To support decision making, this systemapplied Simple Additive Weighting method as an optimal alternative search method based on specifiedcriteriaFrom the results of the research found that the search for optimal alternative of a number ofcandidates for High Leadership Of Pratama with this method can be trusted because of thismathematical method there is a statistical test by looking at the value of criteria previously given tothe alternative. Implementing this system can reduce errors in alternative assessments, facilitateimplementation at all stages and systems more efficiently than traditional systems.